Implementation of English Vocabulary Learning Develop Through Association Word Games at Junior High School - Utamy, Sri Nur; Asnawi; Harianto II; Fadlan, Muhammad Noer; Sabariah, Sabariah; Siregar, Asrul; Susianto, Susianto; Hasanah, Hasanah; Napitupulu, Safrida; Husna, Faisal; Yusuf, Muhammad (International Journal of Educational Research Excellence (IJERE), 2024)
Basically, language is a means of oral and written communication. People use language to express their ideas and desires to others such as when they ask for help from others. According to Danzalan (2016), language allows people to recognize and express their emotions and thoughts. Language is used by humans to recognize and understand each other. As we know, God created humans in various conditions and personalities, so they must interact with each other. As Nursyamsi (2006) states that one way to communicate is through speaking